Verb–noun dissociations in relapsing-remitting multiple sclerosis: verb effects of semantic complexity and phonological relatedness. Issue 1 (2nd January 2017) - Kambanaros, Maria; Messinis, Lambros; Nasios, Grigorios; Nousia, Anastasia; Papathanasopoulos, Panagiotis
ABSTRACT: Background: The last two decades have afforded a small but steady rise in the number of studies exposing language dysfunctions in patients with relapsing remitting multiple sclerosis (RRMS), the most common form of multiple sclerosis however, not much is known about word class naming deficits in this group of individuals. Aim: To explore whether individuals with RRMS show word class naming deficits favouring either nouns or verbs, and if verb accuracy is affected by semantic and phonological verb type. Method: A total of 31 adults with RRMS were compared to 28 demographically matched healthy controls on noun and verb production using the Greek Object and Action Test (GOAT), a picture-based assessment developed for this purpose. Different semantic categories of verbs were investigated such as conceptually/semantically "heavy" verbs (i.e., instrumental verbs, e.g., "sweeping") compared to conceptually/semantically "weaker" verbs (i.e., non-instrumental verbs (NIVs), e.g., "sleeping") and instrumental verbs that were phonologically related to a noun (i.e., name-related instrumental verbs, e.g., "mopping"). Outcome & results: Verbs were significantly more difficult to retrieve than nouns for the RRMS group on production tasks compared to the demographic and intelligence matched healthy participants. Moreover, there was a significant difference between instrumental and NIV production with instrumental verbs more difficult to retrieve than NIVs. In regard to phonological relatedness, non-name-related instrumental verbs were significantly more difficult to retrieve than name-related instrumental verbs. Multiple regression analyses conducted as a separate model for verbs and nouns indicated that performance on the GOAT could not be explained by any of the predictor variables (demographic, clinical, or neurocognitive performance). Conclusion: Based on the results, the grammatical distinction for Greek verbs and nouns seems to be preserved in this group of individuals with RRMS. The naming deficit is probably in the connection between the semantic lexicon and the phonological lexicon. In the case of verbs, the magnitude of the difficulty was larger because of the effects of word frequency on verb retrieval. Overall, poor performance on verb and noun naming may be a marker of incipient cognitive decline, and typical cognitive-linguistic testing is not sensitive or specific enough to capture this phenomenon.